2018
DOI: 10.1038/s41598-018-33906-w
|View full text |Cite
|
Sign up to set email alerts
|

Carnivory in the larvae of Drosophila melanogaster and other Drosophila species

Abstract: Drosophila melanogaster is widely used as a model organism for biological investigations, and food is a major aspect of its ecology and evolutionary biology. Previous studies have shown that this insect can use fruits, yeasts and insect carcasses as its food sources. In this study, we demonstrate that this species is an omnivore, that its larvae can exploit not only fruits and yeast but also foods of animal origin (FAOs), and that larvae consume adult carcasses regularly. FAO-fed larvae develop into adulthood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…In the assay of attraction to injured allospecifics, by contrast, all of the species were attracted to some of the allospecific SOA larvae as compared to random expectation. Although carnivory of D. auraria and D. triauraria has not been examined previously, Yang (2018) observed carnivorous behaviour in several drosophilids including D. melanogaster and D. simulans , supporting the current observation. Also, in Yang (2018), carnivory in drosophilids was tested using a variety of FAOs such as beef, clam, and roasted chicken, but no live food was tested.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the assay of attraction to injured allospecifics, by contrast, all of the species were attracted to some of the allospecific SOA larvae as compared to random expectation. Although carnivory of D. auraria and D. triauraria has not been examined previously, Yang (2018) observed carnivorous behaviour in several drosophilids including D. melanogaster and D. simulans , supporting the current observation. Also, in Yang (2018), carnivory in drosophilids was tested using a variety of FAOs such as beef, clam, and roasted chicken, but no live food was tested.…”
Section: Discussionsupporting
confidence: 87%
“…Traditionally, yeasts associated with plant fermentation comprise the major food source of Drosophila melanogaster Meigen (Diptera: Drosophilidae), a widely used non‐carnivorous model insect (Cooper, 1960; Klaczko et al ., 1983). However, several studies have suggested that D. melanogaster is an omnivorous insect that can also consume a variety of foods of animal origins (FAOs), including carcasses of spiders or insects (Gregg et al ., 1990; Ahmad et al ., 2015; Yang, 2018). Among the FAOs, D. melanogaster larvae regularly consume wandering‐stage conspecifics under crowded laboratory conditions (Vijendravarma et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterol compositions of the three fly organs indicated that, independent of temperatures, flies were feeding on mixed diets containing comparable fractions of plant and yeast components. Interestingly, they also contained a sizable fraction of cholesterol suggesting that flies made occasional use of foods of mammalian origin [19]. Expectantly, the sterol compositon of beginning and end of August collections was similar.…”
Section: Resultsmentioning
confidence: 99%
“…will be more likely to engage in group foraging at higher densities in order to 72 access needed resources. However, as D. melanogaster larval cannibalism is 73 expressed in times of nutritional stress and can involve individuals consuming 74 other larvae (Vijendravarma et al 2013), adult carcasses (Yang 2018) and/or eggs 75 (Ahmad et al 2015; but see Narasimha et al 2019), at higher densities one 76…”
Section: Introduction: 34mentioning
confidence: 99%